2022
DOI: 10.1200/edbk_350751
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities in Prostate Cancer and Approaches to Advance Equitable Care

Abstract: The American Cancer Society estimates approximately 268,490 new cases of prostate cancer and approximately 34,500 deaths caused by prostate cancer in the United States for 2022. Globally, a total of 1,414,259 new cases of prostate cancer and 375,304 related deaths were reported in 2020. Well-documented health disparities and inequities exist along the continuum of care for prostate cancer management—from screening to diagnostic and staging work-up, surveillance, and treatment—ultimately impacting clinical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Similarly, a growing body of evidence advises that omnipresent disparities in prostate cancer outcomes are reduced or eliminated in the context of clinical trials which provide both equal and equitable care. 7 A multiple-cohort study of more than 300 000 patients with prostate cancer found that Black race was not associated with inferior prostate cancerspecific mortality in cohorts from NCI-sponsored randomized clinical trials and the Veterans Affairs health system, while it was associated with increased prostate cancer-specific mortality within the SEER registry, suggesting that with similar access to care and standardized treatment, Black men with nonmetastatic prostate cancer appeared to have comparable stage-forstage prostate cancer-specific mortality to White men. 8 Much literature has been devoted to the challenges of enrollments and inclusion of racial and ethnic minority groups and mar-ginalized demographic groups in the US and corresponding strategies to reduce them.…”
Section: Declining Representation and Reporting Of Racial And Ethnic ...mentioning
confidence: 99%
“…Similarly, a growing body of evidence advises that omnipresent disparities in prostate cancer outcomes are reduced or eliminated in the context of clinical trials which provide both equal and equitable care. 7 A multiple-cohort study of more than 300 000 patients with prostate cancer found that Black race was not associated with inferior prostate cancerspecific mortality in cohorts from NCI-sponsored randomized clinical trials and the Veterans Affairs health system, while it was associated with increased prostate cancer-specific mortality within the SEER registry, suggesting that with similar access to care and standardized treatment, Black men with nonmetastatic prostate cancer appeared to have comparable stage-forstage prostate cancer-specific mortality to White men. 8 Much literature has been devoted to the challenges of enrollments and inclusion of racial and ethnic minority groups and mar-ginalized demographic groups in the US and corresponding strategies to reduce them.…”
Section: Declining Representation and Reporting Of Racial And Ethnic ...mentioning
confidence: 99%
“… 19 Implementing such educational efforts and quality equity metrics into clinical practice and quality improvement projects (eg, monitoring time to treatment and technology utilization across sociodemographic groups) will provide an initial path to mitigate disparities and achieve health equity in radiation oncology. 20 …”
Section: How Can We Address These Disparities In Our Field?mentioning
confidence: 99%
“…Source: GLOBOCAN 2020. [11] Regarding North America and specifically the United States, [12] some reports show an incidence of new cases of prostate cancer (268,490) and 12.84% of deaths (34,500) in the year 2022. In addition, recently a study displayed that there was an increase in the incidence and mortality of prostate cancer in Canada during 1992-2010.…”
Section: Introductionmentioning
confidence: 99%